Răspuns :
a)I. x(x+3)=[tex] (x+1)^{2} [/tex]
[tex] x^{2} [/tex]+3x=[tex] x^{2} [/tex]+2x+1
3x=2x+1
x=1
II.3(x+5)=2(x+8)
3x+15=2x+16
x=1
Rezulta din I si II ca ecuatiile sunt echivalente
b)I. 5x-2(x-3)=2(x+5)
5x-2x+6=2x+10
3x+6=2x+10
x=4
II. x(x+5)=[tex] (x+2)^{2} [/tex]
[tex] x^{2} [/tex]+5x=[tex] x^{2} [/tex]+4x+4
5x=4x+4
x=4
Rezulta din I si II ca ecuatiile sunt echivalente
c)I. 3x+2(x+1)=4(x+2)
3x+2x+2=4x+8
5x+2=4x+8
x=6
II. x(x+3)=[tex] (x+1)^{2} [/tex]+5
[tex] x^{2} [/tex]+3x=[tex] x^{2} [/tex]+2x+1+5
3x=2x+6
x=6
Rezulta din I si II ca ecuatiile sunt echivalente
[tex] x^{2} [/tex]+3x=[tex] x^{2} [/tex]+2x+1
3x=2x+1
x=1
II.3(x+5)=2(x+8)
3x+15=2x+16
x=1
Rezulta din I si II ca ecuatiile sunt echivalente
b)I. 5x-2(x-3)=2(x+5)
5x-2x+6=2x+10
3x+6=2x+10
x=4
II. x(x+5)=[tex] (x+2)^{2} [/tex]
[tex] x^{2} [/tex]+5x=[tex] x^{2} [/tex]+4x+4
5x=4x+4
x=4
Rezulta din I si II ca ecuatiile sunt echivalente
c)I. 3x+2(x+1)=4(x+2)
3x+2x+2=4x+8
5x+2=4x+8
x=6
II. x(x+3)=[tex] (x+1)^{2} [/tex]+5
[tex] x^{2} [/tex]+3x=[tex] x^{2} [/tex]+2x+1+5
3x=2x+6
x=6
Rezulta din I si II ca ecuatiile sunt echivalente